A comparative proteomic-based study identifies essential factors involved in hair follicle growth in inner Mongolia cashmere goats - Rile Nai; Chongyan Zhang; Yuchun Xie; Duhu Man; Haijun Li; Lina Ma; Lu Mi; Meng Zhao; Qier Mu; Lixia Gao; Zhihong Liu; Jinquan Li (BMC Veterinary Research)
Abstract Renowned for its invaluable undercoat, the cashmere goat is well known. The growth of cashmere fibre initiates when the relatively inactive telogen stage transitions to the anagen stage, which involves active proliferation. However, the molecular mechanisms responsible for this process are still unclear. Here, SWATH mass spectrometry (MS), a comparative proteomic analysis, was conducted to examine the proteomic alterations in Inner Mongolia cashmere goat skin samples at two different developmental stages (anagen and telogen). In total, 2414 proteins were detected, with 631 proteins showing differential regulation (503 upregulated proteins and 128 downregulated proteins). Bioinformatic analysis revealed that these proteins, which are differentially regulated, play crucial roles in the pathways associated with metabolism and fatty acids according to the GO and KEGG analyses. Furthermore, interactome analysis revealed that differentially regulated keratins have a crucial impact. The localization of KRT25, KRT71, and KRT82 using immunohistochemistry revealed that these proteins were expressed in the secondary hair follicles of cashmere goat skin. The keratin family plays an irreplaceable and important role in the process of hair follicle growth.